2007
DOI: 10.1117/12.708683
|View full text |Cite
|
Sign up to set email alerts
|

3D reconstruction of highly fragmented bone fractures

Abstract: A system for the semi-automatic reconstruction of highly fragmented bone fractures, developed to aid in treatment planning, is presented. The system aligns bone fragment surfaces derived from segmentation of volumetric CT scan data. Each fragment surface is partitioned into intact-and fracture-surfaces, corresponding more or less to cortical and cancellous bone, respectively. A user then interactively selects fracture-surface patches in pairs that coarsely correspond. A final optimization step is performed aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…In [6], the authors developed an interactive system demonstrated to reconstruct a 5-fragment comminuted bone fracture of the proximal humerus, which relied on bone positioning via a haptic interface. Work by Willis et al [7] involved an automatic system capable of reconstructing bone fractures. However, determination of fragment correspondences was left to a user interaction, which was not discussed in detail within their work.…”
Section: Contribution Of This Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [6], the authors developed an interactive system demonstrated to reconstruct a 5-fragment comminuted bone fracture of the proximal humerus, which relied on bone positioning via a haptic interface. Work by Willis et al [7] involved an automatic system capable of reconstructing bone fractures. However, determination of fragment correspondences was left to a user interaction, which was not discussed in detail within their work.…”
Section: Contribution Of This Workmentioning
confidence: 99%
“…The approach avoids the problem of painstakingly making small refinements to fragment positions which can occur in systems that rely completely on interactive methods [5,6]. It also avoids having to search the very large space of possible fragment matches faced by fully automatic fracture reconstruction systems [7]. Hence, the proposed system leverages domain knowledge through user-specified matches, and it uses automatic surface registration techniques to generate fragment reconstructions that are more accurate than manual methods and more reliable than completely automatic methods.…”
Section: Contribution Of This Workmentioning
confidence: 99%
“…Accurate diagnosis of fracture severity and treatment of the injury are key factors in determining the long-term prognosis for traumatic bone fracture patients. Recent work has focused on developing systems that seek to assist in accurately characterizing fractures (Willis et al 2007). This includes diagnostic systems to assist in assessment of the fracture severity (Liu 2012) and systems that virtually reconstruct complex bone fractures (Chowdhury et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no existing approaches that seek to provide this level of understanding of a bone fracture despite their potential helpfulness to orthopaedic surgeons. However, recent research in Willis et al (2007), Zhou et al (2009), and Liu (2012) provide key technologies for semi-automatic virtual fracture reconstruction that now enable virtual simulation of the fracture event possible.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods require the user to manually reposition fragments, a daunting task for highly comminuted fractures. Willis et al recently reported methodology for semi-automatic reconstruction of highly comminuted bone fractures, developed to aid in treatment planning (Willis et al 2007). The software aligns bone fragment fracture surfaces derived from segmentation of volumetric CT scan data.…”
Section: Introductionmentioning
confidence: 99%